ChemInform Abstract: Revisiting the Solution Structure of Ceric Ammonium Nitrate. Issue 35 (September 2015) - Demars, Thomas J.; Bera, Mrinal K.; Seifert, Soenke; Antonio, Mark R.; Ellis, Ross J.
Abstract Synchrotron X‐ray absorption spectroscopy, XANES, EXAFS, and Raman spectroscopy indicate that aq.